Hypovitaminosis D3, Leukopenia, and Human Serotonin Transporter Polymorphism in Anorexia Nervosa and Bulimia Nervosa. (24th January 2016) - Tasegian, Anna; Curcio, Francesco; Dalla Ragione, Laura; Rossetti, Francesca; Cataldi, Samuela; Codini, Michela; Ambesi-Impiombato, Francesco Saverio; Beccari, Tommaso; Albi, Elisabetta
Abstract : Vitamin D3 has been described to have different extraskeletal roles by acting as parahormone in obesity, diabetes, cancer, cognitive impairment, and dementia and to have important regulatory functions in innate immunity. There are no studies showing extraskeletal changes associated with hypovitaminosis D3 in eating disorders. Methods. We have analyzed the blood of 18 patients affected by anorexia nervosa and bulimia nervosa collected over a 15-month period. We performed a panel of chemical and clinical analyses: the assay of vitamin D3, the immunoblotting of vitamin D receptor and peroxisome proliferator-activated receptor gamma, and the genotyping of 5-hydroxytryptamine transporter linked polymorphic region. Results. We choose 18 patients with a normal blood test profile such as thyroid hormones, hepatic and renal parameters, triglycerides, proteins, vitamin B12, and folic acid. Among these emerged the case of a woman with long-term anorexia nervosa and the case of a woman with long-term bulimia nervosa both complicated by anxiety and depression, severe hypovitaminosis D3, decrease of vitamin D receptor, leukopenia, and 5-hydroxytryptamine transporter linked polymorphic region short allele. Conclusion. The results induce hypothesising that the severe hypovitaminosis D3 might be responsible for the lack of the inflammatory response and the depressive symptoms in patients with long-term eating disorders.